A Technique for Designing and Augmenting Simulation Experiments - Williams, Donald R.; Weeks, David L. (Management Science, 1974)
The technique presented permits the experimenter to eliminate, if possible, a large number of the design points of an experiment. It also permits him to sequentially converge, if necessary, to an entire set of design points or to eliminate design points in which there is little interest. The technique is very flexible with regard to augmentation of levels and/or factors at various stages of the investigation. Thus, it provides a means of designing and augmenting experiments which is particularly suitable to simulation experiments. Furthermore, the analysis of the data at each step in the sequence is performed using the conventional analysis-of-variance techniques.